The Reviewing Concept of Asymmetric Decentralization in The Special Region of Yogyakarta - Triwahyuningsih Triwahyuningsih (Jurnal Daulat Hukum, 2021)
The following research aims to analyze the background of the concept of asymmetric decentralization applied in the Special Region of Yogyakarta and aspects of asymmetric authority in the Special Region of Yogyakarta. This research method is normative legal research which is complemented by field research in the form of interviews with related parties. Using a historical approach (historical approach) and legislation (statute approach) It is concluded that the granting of asymmetric decentralization in DIY is due to philosophical, historical, juridical and sociological. The application of asymmetric decentralization in the Special Region of Yogyakarta in the form of the special authority of DIY includes filling in the positions of Governor and Deputy Governor, Regional Institutions, Culture, Land and Spatial Planning.